2022
DOI: 10.1007/s10708-021-10550-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of access to ICT and food security of the poor in South Africa’s Soshanguve

Abstract: This study discusses access to information and communication technology in the context of food security in Soshanguve, a slum area of The City of Tshwane, the administrative Capital of South Africa. City dwellers access food from retail outlets in a country where dispatching food is a lucrative business. Hence, food price increases pose challenges to urban households. South African Broadcasting Corporation (SABC), other television stations and radio stations broadcast food marketing information through eleven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Specifically, this study found that the use of ICTs can increase the consumption of high‐quality foods, promote dietary diverse among adults, and help combat issues related to overnutrition (Muange & Ngigi, 2021). Another study from South Africa found that ICTs access, such as mobile or landline phones, was positively correlated with household food security (Akinboade et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, this study found that the use of ICTs can increase the consumption of high‐quality foods, promote dietary diverse among adults, and help combat issues related to overnutrition (Muange & Ngigi, 2021). Another study from South Africa found that ICTs access, such as mobile or landline phones, was positively correlated with household food security (Akinboade et al, 2022).…”
Section: Introductionmentioning
confidence: 99%